Farm level cost of reducing nitrate leaching by economic instruments in Croatian farming systems - Ramona Franic; Milan Mesic; Zoran Grgic; John Sumelius (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2002)
Croatian farming systems have become more intensive in recent years. There is some evidence of rising NO3-N-levels in ground water. The aim of the paper is to find possible ways of preventing NO3-levels to rise in Croatian farming systems and their implications from the viewpoint of the manager. More specifically the purpose is to 1. Determine whether Croatian farmers exceed profit maximising levels of N-fertiliser use in maize cultivation and possible influence on NO3-N-levels. 2. To estimate the marginal abatement cost (MAC) at farm level of reducing NO3-N leaching through following economic instruments: a tax on optimal N-doses, a product tax and a Nfertiliser quota, all instruments corresponding to the same abatement level. Based on N-response experiments from field trials for maize N-response curves were derived. A sample of 20 family farms was used to calculate intensity, nutrient content in manure and the prices paid for N and obtained for maize. Profit maximising doses from the field trials were compared with nutrient use on farms. An effluent production function was estimated based on experiments with NO3-N contents in lysimeter water for the same treatments as in the N-response experiments. The results indicate that farmers use higher than optimal levels of N-fertilisers, if the technology and conditions of experimental fields could be applied on the farms and if manure is accounted for. Neglecting the N-content of the manure shows close to optimal nutrient levels. At profit maximising levels the NO3-N level is approximately 14 mg NO3-N/l (62 mg NO3/l) or clearly higher that the critical level stipulated by the nitrate directive (11.3 mg NO3- N/l or 50 mg NO3/l). If the N-content in the manure is taken into account the estimated NO3-N/l level in groundwater is about twice higher than the critical level stipulated by the Nitrate Directive. Through any of the three instruments a 76% NO3- leaching reduction could be obtained. However, it was concluded the quota has the lowest MAC (4.08 ?/mg NO3-N/l or 0.92 ?/mg NO3/l), followed by the N-fertiliser tax (16.16 ?/mg NO3-N/l or 3.65 ?/mg NO3/l) and the product tax in third place (41.25 ?/mg NO3-N/l or 9.32 ?/mg NO3/l). Management practices that may increase yield level and correspondingly NO3-leaching in the short and long run were identified. One way to achieve a quick improvement would be a system of cross compliance stipulating a code of good agricultural practices.
Keywords: 330; Düngemittel; Umweltabgabe; Umweltauflage; Stickstoffdünger; Nitrat; Landwirtschaft; Produktionskosten; Kroatien